Methodological issues in longitudinal studies: vestibular schwannoma growth rates in neurofibromatosis 2 - Baser, M (BMJ Group, 2005)
Four longitudinal studies of vestibular schwannoma (VS) growth rates in neurofibromatosis 2 (NF2) have yielded very different results on the relationship of VS growth rates to age. The studies had different patient eligibility criteria, indices of VS growth rates, VS volumetric methods, and sample sizes. We reanalysed data from two of the longitudinal studies and used data from the population based United Kingdom NF2 Registry to determine the most likely reason for the different results and the actual relationship of VS growth rates to age. We found that the eligibility criterion in one study caused selection bias for slower growing VS. The proper interpretation of the results from the four studies is that VS growth rates in NF2 are highly variable but tend to decrease with increasing age. Clinical trials for VS in NF2 should focus on younger patients because VS growth rates tend to decrease with increasing age, and because faster growing VS are more likely to be excised with increasing age than slower growing VS.